Low-Tech Visual Scaffolds for High Gains: Cue-Card Instruction Elevates Grade-8 EFL Speaking in Rural Central Sulawesi - Asdar, Asdar; Kamaruddin, Abdul; Erniwati, Erniwati (Pascasarjana Universitas Negeri Makassar, 2025)
Developing communicative competence in under-resourced classrooms remains a persistent challenge for English as a Foreign Language (EFL) teachers. Grounded in Dual-Coding and Multimedia-Learning theories, this study investigated the impact of cue-card scaffolding on the speaking performance of Grade-8 students at a remote junior-high school in Central Sulawesi, Indonesia. Using a pre-experimental one-group pre-test–post-test design, 21 students completed a baseline oral test, participated in seven 80-minute lessons that progressed from image-only cards to situational grids, and sat for an equivalent post-test. Performances were rated with a four-category analytic rubric (fluency, vocabulary, grammar, pronunciation) by two trained raters (α = .89; r = .91). Mean scores improved from 46.14 to 59.14, yielding a mean gain of 13 points and a large practical effect (Cohen’s d = 1.40). A paired-samples t test showed the improvement was statistically significant (t = 9.92, df = 20, p < .001). Score dispersion narrowed, indicating benefits for both lower- and higher-proficiency learners. Classroom observations revealed increased lexical range and reduced hesitation, supporting theoretical claims that visual–verbal integration lowers cognitive load. The findings confirm cue cards as a cost-effective alternative to digital media for advancing oral proficiency in bandwidth-constrained contexts. Implications for lesson planning, teacher training, and equity-oriented language policy are discussed.